Gastrectomy correlates with increased risk of pulmonary tuberculosis: A population-based cohort study in Taiwan. Issue 27 (July 2018) - Cheng, Kao-Chi; Liao, Kuan-Fu; Lin, Cheng-Li; Lai, Shih-Wei
Abstract : Abstract: The objective to assess the association between gastrectomy and the risk of pulmonary tuberculosis among patients without gastric cancer in Taiwan. There were 762 subjects with newly performing gastrectomy as the gastrectomy group since 2000 to 2012, and 2963 randomly selected subjects without gastrectomy as the non-gastrectomy group. Subjects with history of pulmonary tuberculosis or gastric cancer before the index date were excluded. Both gastrectomy and non-gastrectomy groups were matched with sex, age, and comorbidities. The incidence of pulmonary tuberculosis was assessed in both groups. The multivariable Cox proportional hazards regression model was used to assess the hazard ratio and 95% confidence interval for risk of pulmonary tuberculosis associated with gastrectomy. The overall incidence of pulmonary tuberculosis was 1.97-fold greater in the gastrectomy group than that in the non-gastrectomy group. The multivariable Cox proportional hazards regression analysis demonstrated that the adjusted HR of pulmonary tuberculosis was 1.97 for the gastrectomy group, compared with the non-gastrectomy group. Male sex, age (increase per 1 year), chronic obstructive pulmonary disease, and splenectomy were other factors that could be related to pulmonary tuberculosis. Gastrectomy is associated with 1.97-fold increased risk of pulmonary tuberculosis among patients without gastric cancer.